2020
DOI: 10.1182/blood-2020-136900
|View full text |Cite
|
Sign up to set email alerts
|

Evans' Syndrome in Adults: An Observational Multicentre Study

Abstract: Evans' syndrome is a rare condition (estimated prevalence of 1-9 per million), characterized by the association (concomitant or not) of immune thrombocytopenia (ITP), with autoimmune hemolytic anemia (AIHA), and/or autoimmune neutropenia (AIN). Here we investigated 106 adult patients (male to female ratio 0.89, median age 50 years) followed for a median of 7.5 years in 12 European tertiary centers. Hematological data and associated conditions at diagnosis, treatments, complications, and outcome were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Regarding autoimmunity testing, almost 90% of tested subjects had a positive direct Coombs test and non-organ specific autoantibodies were detected in over 50% of cases (e.g., ANA, ENA, lupus anticoagulant). 7 LS, also referred to as morphea, is an uncommon inflammatory and fibrotic disease of the skin and subcutis. LS encompasses a wide spectrum of clinical variants ranging from solitary skin lesions with minimal discomfort to severe subtypes such as generalized or linear morphea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding autoimmunity testing, almost 90% of tested subjects had a positive direct Coombs test and non-organ specific autoantibodies were detected in over 50% of cases (e.g., ANA, ENA, lupus anticoagulant). 7 LS, also referred to as morphea, is an uncommon inflammatory and fibrotic disease of the skin and subcutis. LS encompasses a wide spectrum of clinical variants ranging from solitary skin lesions with minimal discomfort to severe subtypes such as generalized or linear morphea.…”
Section: Discussionmentioning
confidence: 99%
“…Evans’ syndrome is an autoimmune condition that presents with two or more cytopenia, which usually include ITP and warm (about 37°C) AIHA which is mainly characterized by extravascular hemolysis in the spleen. 6 , 7 Warm AIHA is diagnosed in the presence of anemia, usually macrocytic and of variable intensity, reticulocytosis, and a positive direct Coombs test positive for warm anti-IgG antisera with panreactive specificity or anti-IgG plus C3 at low titer. 7 Depending on disease severity and time of evaluation, increased serum LDH and indirect bilirubin, and decreased haptoglobin are frequent findings in patients with AIHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely attributed to the rarity of ES, especially in populations that refuse blood transfusion. The use of ESAs in isolated AIHA has been examined in greater detail; however, varying outcomes are described in small multicentric studies [ 3 ]. In a single case report, it was theorized that the mechanism of ESAs in AIHA is secondary to both stimulations of RBC production and the ability to decrease the total amount of autoantibodies present on RBCs by increasing the amount of antibody-free erythrocytes in circulation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary ES is usually associated with a wide array of underlying disorders, including systemic lupus erythematosus (SLE), autoimmune hepatitis, chronic lymphocytic leukemia, and autoimmune lymphoproliferative syndrome (ALPS) [ 1 , 2 ]. The exact prevalence of ES is unknown; however, rough estimates note one to nine persons per million based on small retrospective cohorts and observational studies [ 3 ]. A retrospective review in Denmark identified 242 patients diagnosed with ES from 1977 to 2017, noting a five-year mortality rate of 38% and a median survival of 1.7 years in patients with secondary ES specifically [ 4 ].…”
Section: Introductionmentioning
confidence: 99%